Second-order differential subordinations on a class of analytic functions defined by Rafid-operator - Akgül, A. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
The purpose of the present paper is to introduce a new class of analytic functions by using the Rafid-integral operator andobtain some subordination results.